Pola Asuh dalam Religious Belief Orang Tua di Surakarta - Qonitah Faizatul Fitriyah; Sri Katoningsih; Tri Asmawulan; Isnaini Budi Hastuti (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2022)
Literature argues that religion has a role in the application of parenting styles. However, we need to interrogate what kind of parenting is in the religious belief of parents. This study aims to determine the role of religious beliefs in shaping parenting style in Surakarta. This research method uses a qualitative method using a case study research design that aims to explore child care. Data collection techniques used face-to-face interviews and video calls with snowball sampling. The data analysis technique used the Miles and Huberman technique. The results of this study are parenting in religious beliefs in parents tends to lead to an authoritarian style, with the aim of introducing rules and boundaries for children to avoid the impact of negative behavior. These results indicate that religious belief becomes the direction and reference for parents as a disciplinary decision in the upbringing of children.